Rhizosphere Microbial Community Diversity and Function Analysis of Cut Chrysanthemum During Continuous Monocropping - Wang, Tan; Yang, Kexin; Ma, Qingyun; Jiang, Xu; Zhou, Yiqing; Kong, Delong; Wang, Zhiye; Parales, Rebecca E.; Li, Lin; Zhao, Xin; Ruan, Zhiyong (Frontiers in Microbiology, 2022)
As an ornamental flower crop, the long-term continuous monocropping of cut chrysanthemum can cause frequent occurrence of diseases, seriously affecting the quality of cut chrysanthemum. The rhizosphere microbial community plays an important role in maintaining the healthy growth of plants, whereas the composition and dynamics of rhizosphere microbial community under continuous monocropping of cut chrysanthemum have not been fully revealed. In this study, Illumina MiSeq high-throughput sequencing platform was used to monitor the dynamic changes of rhizosphere microbial communities in four varieties of cut chrysanthemum during 0–3 years of monocropping, and the soil physicochemical properties and soil enzyme activities were also determined. Results showed that the fungal community richness significantly increased with the monocropping period, whereas the bacterial community had no significant change. Continuous monocropping altered the profiles of the bacterial and fungal community, leading to variation of community beta-diversity. Continuous monocropping significantly reduced the relative abundance of Actinomycetes in the rhizosphere and the relative abundance of beneficial taxa such as Pseudomonas, Bacillus, Rhizobium, and Mortierella at the genus level but increased the abundance of plant pathogens such as Fusarium, Alternaria, and Rhizoctonia in the rhizosphere of cut chrysanthemums. Meanwhile, redundancy analysis showed that the content of ammonium nitrogen and salt was the most important factor affecting the beta-diversity in the rhizosphere microbial community. Thus, we hypothesized that the decrease and increase of these taxa and the decrease of soil physical and chemical properties hindered the continuous monocropping of cut chrysanthemum.